THE USE OF DICTOGLOSS TECHNIQUE THROUGH JOOX APPLICATION TO IMPROVE STUDENTS’ LISTENING SKILL - Jusmaniar N; Rizka Indahyanti; Nur Aisyah J (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2023)
The research design used was quantitative research with a quasi-experimental through 2 classes, namley the experimental class and the control class. The number of samples in this research consisted of 22 students in class XI.I and 22 students also in XI. 2. Instrument used to collect data were listening tests in the form fill in the blank, multiple choice and questionnaires. The resullts showed that the average value of the pre-test experimental class XI.I is 67.13. While the average value of the post-test is 85.13.Which is higher than the pre-test. While the average value in control class XI.2 is 66.25 and the post-test value is 77.69. This mean that there was a significant improvement in experimental class using JOOX Application than control class who do not use the JOOX Application. As for the result of data average students interest is 62,5%. It can be seen that the average score student questionnaire indicates that students are interested or students agree with the positive statements of the questionnaire.